PENGARUH P5 TERHADAP KEMAMPUAN BERPIKIR KRITIS MURID SMA: SEBUAH STUDI KUANTITATIF DI JAKARTA TIMUR - Ananto, Purnomo; Dwilanisusantya, Carissa; Andriyana, Andriyana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
The Strengthening of the Pancasila Student Profile (P5) Project is one of the implementations of the Merdeka Curriculum aimed at shaping students who are not only intellectually intelligent but also possess critical thinking skills and strong character based on the values of Pancasila. This study aims to determine high school students' perceptions of the contribution of P5 in developing critical thinking abilities. The method used is quantitative with a survey approach using a Likert scale questionnaire, which was distributed to 65 high school students in East Jakarta. The analysis results show that the 65% of students experienced a positive impact from the implementation of P5 on enhancing their critical thinking skills. However, 35% of students also gave negative responses, indicating the need for further evaluation of the program’s implementation, particularly regarding teachers' understanding, the selection of themes, as well as the strategies and assessment methods used. These findings are supported by literature that states that the success of P5 heavily depends on the quality of planning, teacher training, and innovative and contextual learning designs. Therefore, improving teacher capacity and systematic evaluation are crucial to maximize P5’s role in shaping students with critical thinking abilities.